Patient‐reported outcome measure for obstructive sleep apnea: Symptoms, Tiredness, Alertness, Mood and Psychosocial questionnaire: Preliminary results. (20th December 2019) - Mehta, Nishchay; Mandavia, Rishi; Patel, Ankit; Zhang, Henry; Liu, Zi‐Wei; Kotecha, Bhik; Veer, Vik
Abstract: Obstructive sleep apnea (OSA) is a common chronic condition that has a significant impact on the biopsychosocial aspects of the patient's life. There is currently no psychometrically validated patient‐reported outcome measure to assess the impact of this condition on the health‐related quality of life. We designed a novel instrument based on common patient statements, prioritized by patient preference. Sixty‐three patients with OSA and 33 participants with no symptoms of sleep‐disordered breathing were asked to complete a 20‐item initial questionnaire. The acceptability, reliability and validity of the instrument were assessed using known psychometric techniques. The instrument had strong acceptability and was completed within 180 s with no missing data. Five items were removed as they had a high ceiling factor. A further three items were removed as they did not represent the central construct uniquely. The final 12‐item instrument had high internal consistency (Cronbach's alpha 0.91), strong test–retest reliability ( p  = .83) and high discriminant validity when comparing mean total scores of controls (6.88; 95% confidence interval [CI], 4.67–9.08) and those with OSA (31.39; 95% CI, 27.94–34.84) ( p  < .001). Further studies are planned to help validate this instrument for clinical use.